ANALISIS PENGARUH SEKTOR PARIWISATA TERHADAP TINGKAT PENGANGGURAN TERBUKA DI PROVINSI DIY (DAERAH ISTIMEWA YOGYAKARTA) TAHUN 2015-2019 - Nabil, Daffa Alif; Wiguna, Atu Bagus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Tourism has become a priority sector in Indonesia's economic development. Tourism is also expected to be the main driver in accelerating economic growth in Indonesia through job creation and business opportunities to overcome unemployment in Indonesia. This study aims to determine the effect of the variable number of hotel units, the number of restaurant units, the number of foreign tourists, and the number of domestic tourists on open unemployment in the Province of DIY. The object of this study was 5 Regencies/Cities in DIY in 2015-2019, while the data analysis used was multiple linear regression using SPSS 20. The results of the study found that the number of hotels, restaurants, and government spending had a significant negative effect on open unemployment. The number of foreign tourists and domestic tourists has a significant positive effect on Open Unemployment.